Accountability for Presentation of Financial Statements Based on ISAK No. 35 with Maqashid Syariah Perspective: Case Study on Khusnul Yaqin Wage Orphanage Foundation - Dewy Titik Murtosyiah; M. Dliyaul Muflihin; Ade Irma Suryani Lating; Nandha Nur Jagadhitawati (Ta'amul: Journal of Islamic Economics, 2023)
This study examines the "Accountability of Presentation of Financial Statements Based on ISAK No. 35 with the Maqashid Syariah Perspective" at the Khusnul Yaqin Wage Orphanage Foundation. The research utilized qualitative methods, gathering data through interviews with foundation management, including the chairman, secretary, treasurer, and donors, and analyzing financial reports. The findings reveal that the foundation's management was unfamiliar with ISAK No. 35, resulting in non-compliance with these standards. However, the foundation demonstrated proper accountability in accordance with the principles of maqashid sharia, encompassing hifdz ad-din, hifdz an-nas, hifdz al-aql, hifdz al-mal, and hifdz an-nasb. Despite some challenges, the foundation is striving to improve accountability. The study recommends that orphanages adopt relevant accounting standards for financial reporting and enhance transparency through measures like establishing bulletin boards or websites to disclose financial information. Implementing these suggestions will lead to improved accountability and more effective financial management for orphanages in the future.